Expanding Export Markets for Vietnamese Dragon Fruit (International Journal of Scientific Research and Management (IJSRM), 2025)
Dragon fruit is one of the main fruits of Vietnam, bringing high economic value and contributing significantly to agricultural export turnover. However, Vietnam’s dragon fruit exports are facing many challenges. The decline in demand from China due to the country’s increased domestic production, combined with technical barriers and strict phytosanitary requirements from major markets, has reduced export turnover. The lack of solidity in production linkages and limitations in post-harvest preservation technology are also weaknesses that need to be overcome. In this context, the study proposes many solutions to expand export markets. Solutions focus on improving product quality, complying with international standards, investing in preservation and deep processing technology, promoting product marketing to new markets, as well as taking advantage of free trade agreements to reduce costs and improve export efficiency.